Crystal structure of tolylfluanid - Seonghwa Cho (Acta Crystallographica Section E, 2014)
The title compound, C10H13Cl2FN2O2S2 {systematic name: N-[(dichlorofluoromethyl)sulfanyl]-N′,N′-dimethyl-N-p-tolylsulfamide}, is a well known fungicide. The dihedral angle between the mean plane of the dimethylamino group and that of the benzene ring is 32.3 (3)°. One Cl atom and one F atom of the dichlorofluoromethylthio group are disordered over two sets of sites with an occupancy ratio of 0.605 (9):0.395 (9). In the crystal structure, two C—H...Cl hydrogen bonds link adjacent molecules, forming dimers with R22(14) loops. C—H...O hydrogen bonds link pairs of dimers into chains along the b-axis direction. These chains are joined by an additional C—H...O contact, generating a sheet in the ab plane.